Human Fumarate Hydratase Is Dual Localized by an Alternative Transcription Initiation Mechanism. (6th May 2016) - Dik, Ekaterina; Naamati, Adi; Asraf, Hadar; Lehming, Norbert; Pines, Ophry
Abstract : Schematic model of human FH (fumarate hydratase) distribution mechanism. A) FH is transcribed from a single gene harboring a broad type promoter. Transcription starts from various transcription start sites (TSS), creating different length mRNAs. B) All mRNAs harboring a sequence longer than 15 nt upstream of the first AUG, will be translated from the first AUG (left, orange arrow). These will give rise to the MTS (mitochondrial targeting sequence) harboring FH which will be directed to the mitochondria. C) mRNAs which are transcribed closer to the first ATG or after, will be translated from the second AUG (right, blue arrow). Abstract: Fumarate hydratase (FH, fumarase), is a tricarboxylic acid cycle enzyme localized in the mitochondrial matrix. However, a common theme, conserved from yeast to human, is the existence of a large cytosolic population of FH. FH has been shown to function as a tumor suppressor gene and is now implicated in various diseases. We have previously indicated that the cytosolic echoform of FH has a role in the DNA damage response and specifically in the response to DNA double strand breaks. In fact, recently FH has been shown to be involved in histone demethylation. Therefore, it has become important to understand the underlying mechanism of FH dual subcellular location in human cells. We revealed that in human cells, in contrast to yeast, the FH gene encodes two gene products, one containing and one lacking the mitochondrial targeting sequence. On the basis of expression of endogenous wild‐type FH and mutant FH cDNAs from plasmids, RT‐PCR, RACE to determine the 5′ termini of FH mRNAs, and mass spectrometry of FH products, we show that the mechanism of FH distribution is alternative transcription initiation from a broad promoter. This is contrary to the suggested mechanism for rat liver cells which had claimed alternative translation initiation.